Thoracic Segmental Spinal Anesthesia - Simanjuntak, Alvina; Sudadi, Sudadi; Mahmud (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Thoracic segmental spinal anesthesia (TSSA) is a regional anesthesia technique that is increasingly used as an alternative to general anesthesia, especially for high-risk patients undergoing abdominal and thoracic surgeries. TSSA offers significant benefits, including better hemodynamic stability and a reduction in postoperative side effects such as nausea, vomiting, and respiratory depression. This technique also provides more optimal pain control and facilitates faster recovery, particularly in terms of postoperative mobilization and gastrointestinal function recovery. However, the use of TSSA requires a deep understanding of the relevant anatomy, physiology, and pharmacology to avoid complications such as iatrogenic injury or excessive spread of anesthesia. With the right understanding, TSSA can reduce the need for large volumes of local anesthetics, accelerate recovery, and deliver better outcomes in various surgical procedures. Further development of practice guidelines and research related to TSSA is also necessary to maximize its benefits in improving anesthesia safety and effectiveness in high-risk patients.